2022
DOI: 10.1039/d2ta02049a
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent cationic and anionic mixed redox of an Sb2S3 cathode toward high-capacity aluminum ion batteries

Abstract: The conventional cationic redox centers of transition-metal-based cathodes are reaching their theoretical capacity limit which cannot match the ultra-high specific capacity contributed by the three-electron transfer reaction of Al anode...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…While in the research of antimony sulfide, Sb 2 S 3 , serial characterizations have confirmed that Sb 2 S 3 undergoes multivalent cationic and anionic mixed redox reactions in RAIBs. 19 In particular, antimony-based cations can be oxidized to the highest valence (+5) and they exist in the form of [SbCl 4 ] + cations, which further confirms the inference from metal antimony. Meanwhile, the graphene aerogel (GA) interlayer with dual functions of a physical barrier and chemical adsorption effectively blocks the diffusion of antimony-based cationic charge products and achieves excellent electrochemical performance.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…While in the research of antimony sulfide, Sb 2 S 3 , serial characterizations have confirmed that Sb 2 S 3 undergoes multivalent cationic and anionic mixed redox reactions in RAIBs. 19 In particular, antimony-based cations can be oxidized to the highest valence (+5) and they exist in the form of [SbCl 4 ] + cations, which further confirms the inference from metal antimony. Meanwhile, the graphene aerogel (GA) interlayer with dual functions of a physical barrier and chemical adsorption effectively blocks the diffusion of antimony-based cationic charge products and achieves excellent electrochemical performance.…”
Section: Introductionsupporting
confidence: 64%
“…The achievement of superior electrochemical performance is not only because the successfully prepared carbon shell suppressed the diffusion of the charging product, but also because the 3D rich-pored graphene aerogel (GA) interlayer strongly adsorbed and inhibited the shuttle effect of the charging product. 19 GA interlayer contribution to the battery capacity is very small and is only 14.5 mA g −1 at the charge cut-off voltage of 1.8 V (Fig. S2†).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak could be attributed to the surface-adsorbed oxygen. 65 This hump is more prominent in Al-doped Sb 2 S 3 samples, possibly due to oxidation of Al exposed to the surface. Two sets of peaks which can be deconvoluted to S 2p 1/2 and S 2p 3/2 are observed in the high-resolution sulfur spectra [Fig.…”
Section: Resultsmentioning
confidence: 98%
“…[20,21] Another major issue is the underrepresented capacity, which can be attributed to the fact that conventional cationic redox centers of TMCs can only provide stepwise single-electron transfer and are reaching the theoretical capacity limit. [22,23] When it comes to these challenges, engineering elevated interface reactions and corresponding adsorption-intercalation processes between charge-carriers and host materials is conducive for improving reaction potential and attaining deeper capacity release. At present, a series of "water in salt" electrolytes (WISEs) have been proposed by dissolving ultrahigh concentration of corrosive salt in water, which introduce crowded charge-carriers at the interface of host material to establish a redox process with higher reaction potential.…”
Section: Introductionmentioning
confidence: 99%